Front Cover: Si@SnS2–Reduced Graphene Oxide Composite Anodes for High‐Capacity Lithium‐Ion Batteries (ChemSusChem 23/2019). Issue 23 (26th November 2019) - Dai, Jinyan; Liao, Jiang; He, Minyi; Yang, Mengmeng; Wu, Kaipeng; Yao, Weitang
Abstract : The Front Cover shows the crystal structure of Si@SnS2 ‐rGO and the combination mode of crystal translation. It shows excellent cycle stability (1480.1 mAh g −1 at 200 mA g −1 after 200 cycles) and good magnification (423.5 mAh g −1 at 3000 mA g −1 after 600 cycles) and has better performance than similar materials. More information can be found in the Full Paper by J. Dai et al. on page 5092 in Issue 23, 2019 (DOI: 10.1002/cssc.201902839 ).